Brønsted Acid Catalyzed Tandem Defunctionalization of Biorenewable Ferulic acid and Derivates into Bio‐Catechol. Issue 8 (21st January 2020) - Bomon, Jeroen; Van Den Broeck, Elias; Bal, Mathias; Liao, Yuhe; Sergeyev, Sergey; Van Speybroeck, Veronique; Sels, Bert F.; Maes, Bert U. W.
Abstract: An efficient conversion of biorenewable ferulic acid into bio‐catechol has been developed. The transformation comprises two consecutive defunctionalizations of the substrate, that is, C−O (demethylation) and C−C (de‐2‐carboxyvinylation) bond cleavage, occurring in one step. The process only requires heating of ferulic acid with HCl (or H2 SO4 ) as catalyst in pressurized hot water (250 °C, 50 bar N2 ). The versatility is shown on a variety of other (biorenewable) substrates yielding up to 84 % di‐ (catechol, resorcinol, hydroquinone) and trihydroxybenzenes (pyrogallol, hydroxyquinol), in most cases just requiring simple extraction as work‐up. Abstract : Ferulic acid, a bio‐renewable compound derived from rice bran, has been transformed in catechol, a major commodity chemical, using HCl and water. The protocol is applicable to a variety of other (biorenewable) substrates.